Donor-acceptor pair quantum emitters in hexagonal boron nitride - Tan, Qinghai (2022)
Quantum emitters are needed for a myriad of applications ranging from quantum sensing to quantum computing. Hexagonal boron nitride (hBN) quantum emitters are one of the most promising solid-state platforms to date due to their high brightness and stability and the possibility of a spin-photon interface. However, the understanding of the physical origins of the single-photon emitters (SPEs) is still limited. Here we report dense SPEs in hBN across the entire visible spectrum and present evidence that most of these SPEs can be well explained by donor-acceptor pairs (DAPs). On the basis of the DAP transition generation mechanism, we calculated their wavelength fingerprint, matching well with the experimentally observed photoluminescence spectrum. Our work serves as a step forward for the physical understanding of SPEs in hBN and their applications in quantum technologies.